Local drivers and dynamics of youth radicalisation in Bangladesh / Bangladesh Institute of Peace and Security Studies. - Bangladesh Institute of Peace and Security Studies; Bangladesh Institute of Peace and Security Studies (DOHS, Baridhara: Bangladesh Institute of Peace and Security Studies, 2017)
Study with reference to Dhaka, Bangladesh.
Includes bibliographical references (pages 76-78).
Keywords: Youth and violence -- Bangladesh -- Dhaka; Radicalism -- Bangladesh -- Dhaka